A composite, isotopically-depleted peridotite and enriched pyroxenite source for Madeira magmas: Insights from olivine - Gurenko, Andrey A.; Geldmacher, Jörg; Hoernle, Kaj A.; Sobolev, Alexander V. (Lithos, 2013)
The Madeira and Canary island/seamount chains represent two adjacent hotspot tracks in the eastern North Atlantic, which were derived from mixed peridotite–pyroxenite mantle sources. They possess systematically different Sr–Nd–Pb, Os and Hf isotope signatures, implying mixing of DMM-, HIMU- and EM-type components from different mantle lithologies. The lithological nature of these postulated mantle endmembers (e.g., if formed by peridotite, pyroxenite and/or eclogite) is still a subject of debate. We studied the chemical composition of olivine phenocrysts (focusing on their Ni, Mn and Ca concentrations) from the lavas covering the entire volcanic history of the Madeira Archipelago (~0–5Ma). We demonstrate that Ni×FeO/MgO and Mn/FeO ratios and Ca-concentrations of olivine correlate with Sr, Nd and Pb isotopic compositions of their host lavas. The amounts of peridotite- and pyroxenite-derived melt fractions in the parental Madeira magmas were inferred from olivine compositions and independently confirmed by modeling of two-component source melting using trace elements. Our calculations demonstrate that the amount of recycled crust (=eclogite) in the Madeira magma source varies but does not exceed ~10%. Strong linear relationships between chemical composition of olivine and radiogenic isotopes of the host lavas allow us to determine the isotopic composition of peridotite and pyroxenite endmembers of the Madeira hotspot. The peridotite endmember has a highly depleted isotopic composition 87Sr/86Sr=0.7022–0.7026, 143Nd/144Nd=0.5132–0.5135, 206Pb/204Pb=17.4–18.6, 207Pb/204Pb=15.4–15.49, and 208Pb/204Pb=36.8–38.2, whereas the pyroxenite endmember has an enriched composition 87Sr/86Sr=0.7031–0.7035, 143Nd/144Nd=0.5127–0.5130, 206Pb/204Pb=19.9–21.3, 207Pb/204Pb=15.59–15.69, and 208Pb/204Pb=39.6–41.2. Our new data confirm the existence of recycled (pyroxenitic) lithology in the Madeira magma source that was previously interpreted to represent relatively young (<1Ga) recycled oceanic crust. The isotopically depleted, DMM-like (peridotitic) component sampled by the younger post-erosional stage magmas is thought to reflect the ultramafic portion of the recycled oceanic lithosphere, whereas the HIMU-type pyroxenite of similar age to the peridotite is derived from recycled oceanic crust. Combining our new results with the data from the Canary hotspot, we conclude that the <1Ga recycled crustal component is common to both plume sources. The Canary volcanism also reflects the presence of older (>1Ga) recycled crust and a contribution from African subcontinental lithosphere. •Nickel, Mn and Ca in olivine represent powerful tracers in unraveling deep mantle processes.•Isotopically depleted peridotite and enriched pyroxenite compose the Madeira magma source.•The amount of the recycled crust in the Madeira magma source varies but does not exceed ~10%.•The recycled crust endmember appears to be common to both the Madeira and Canary hotspots.